Witchcraft allegations and untouchability as forms of violence upon women in Nepal: A 7-year study. (September 2021) - Nepal, Samata; Atreya, Alok; Nepal, Binu; Shah, Richa; Dhital, Rolina; Aryal, Shreyashi
The Nepalese constitution guarantees equal rights to both men and women regardless of caste, race, or ethnicity. However, the centuries-old superstitious practice of caste-based hierarchy in the Hindu community and discrimination against people of lower caste are still prevalent. Furthermore, witchcraft allegations are also not uncommon. Both these practices are derogatory and humiliating and violate human rights, and the law can penalise them in both instances. Due to the intersection of gender and caste, women often face multiple forms of discrimination and violence as the patriarchal society considers them a weaker gender. The present study aimed to see the trend of crimes upon women reported by Nepal Police in the form of witchcraft allegations and untouchability between the fiscal years 2013/14 and 2019/20.